Effect of ivermectin® on biometric characteristics and organ biomarkers of African catfish Clarias gariepinus. Issue 1 (2nd January 2020) - Odo, Ursula Ugonna; Christian Ezeoyili, Ifeanyi; Aguzie, Ifeanyi Oscar; Oluah, Stanley Ndubuisi; Madu, Josephine; Nwani, Christopher Didigwu
ABSTRACT: Ivermectin® (IVM) is one of the most widely used antiparasitic drugs in human and veterinary medicine. This study assesses the effect of IVM on biometric characteristics and organ biomarkers of African catfish, Clarias gariepinus . Fish were exposed to 0.007, 0.013 and 0.033 mg/L of IVM and the brain, gill and liver were sampled on days 1, 7, 14, 21 and after 7 – day recovery. A mixed trend was observed in the values of condition factor and hepatosomatic index. There was concentration- and duration-dependent significant increase in the activities of alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase in the tissues. While lipid peroxidation in the brain, liver and gill of the fish increased, activities of catalase, superoxide dismutase and glutathione peroxidase declined. IVM induced biochemical, oxidative stress, and biometric alterations in C. gariepinus juveniles. Thus, the use of the drug in aquaculture for the control of fish parasites requires stringent precautions.